Kontestasi Potensi Ideologi Kebangsaan di Kalangan Pelajar Kota Pontianak - Firdaus Achmad; Syahbudi Syahbudi (AT-TURATS, 2019)
Ideally, as an educational institution storied college, the College of Islamic Studies (IAIN) Pontianak to be one of the pioneers of the application of critical pedagogy. Education policies are applied, ranging from the highest level of academic leadership to the faculty level, should be in favor of the interests of the promotion and development of critical and creative power of students. Alignments it certainly requires the provision of a space for dialogue in some parts of the establishment of policies that touch the actual existence of tendency of students, such as: the formulation of academic handbook, curriculum design, the determination of the order of the lectures, and learning contracts. The focus of research is, Virtualization Critical Pedagogy in the High School Environment State Islamic Pontianak. Of the focus of this study the authors formulate three research questions, namely: 1.How does an understanding of the technical implementation of environmental education at academic community's IAIN Pontianak? 2. How technical education policies implemented by managers in environmental education IAIN Pontianak? 3. How is the academic community's response to the technical education in environmental policy IAIN Pontianak? After making the process of reading, interpretation and critical reflection, the facts and research data, using the method of critical hermeneutics manifold philosophical hermeneutics in general the authors conclude, that there has been no attempt vitalization (strengthening) of critical pedagogy in the IAIN Pontianak. It is caused by a lecturer who is still dominating authority in themanagement of the learning process. In particular, the authors conclude: 1. IAIN Pontianak understanding of the academic community about the technical implementation of education remains intact in the form of the building ideas, both theoretical and potentially authoritative. 2. Technical Education in Environmental Policy IAIN Pontianak not provide space for dialogue which involves students and tend not to be based on the results of academic studies. 3. Manager's response to the educational system Technical Education in Environmental Policy IAIN Pontianak not very positive, as they deem less populist and less and less in favor of the interests of the implementation of the facilitative ideal education. Meanwhile, students understand and interpret technical education policies as a form of intellectual oppression. The recommendations in this study the authors offer ideas shaped paradigmatic. Recommendations meant more authors addressed to the managers of educational systems, is critical pedagogy -based educational paradigm.